Haemodynamics and serial risk assessment in systemic sclerosis associated pulmonary arterial hypertension. Issue 4 (18th October 2018) - Weatherald, Jason; Boucly, Athénaïs; Launay, David; Cottin, Vincent; Prévot, Grégoire; Bourlier, Delphine; Dauphin, Claire; Chaouat, Ari; Savale, Laurent; Jaïs, Xavier; Jevnikar, Mitja; Traclet, Julie; et al.
The prognostic importance of follow-up haemodynamics and the validity of multidimensional risk assessment are not well established for systemic sclerosis (SSc)-associated pulmonary arterial hypertension (PAH). We assessed incident SSc-PAH patients to determine the association between clinical and haemodynamic variables at baseline and first follow-up right heart catheterisation (RHC) with transplant-free survival. RHC variables included cardiac index, stroke volume index (SVI), pulmonary arterial compliance and pulmonary vascular resistance. Risk assessment was performed according to the number of low-risk criteria: functional class I or II, 6-min walking distance (6MWD) >440 m, right atrial pressure <8 mmHg and cardiac index ≥2.5 L·min −1 ·m −2 . Transplant-free survival from diagnosis (n=513) was 87%, 55% and 35% at 1, 3 and 5 years, respectively. At baseline, 6MWD was the only independent predictor. A follow-up RHC was available for 353 patients (median interval 4.6 months, interquartile range 3.9–6.4 months). The 6MWD, functional class, cardiac index, SVI, pulmonary arterial compliance and pulmonary vascular resistance were independently associated with transplant-free survival at follow-up, with SVI performing better than other haemodynamic variables. 1-year outcomes were better with increasing number of low-risk criteria at baseline (area under the curve (AUC) 0.63, 95% CI 0.56–0.69) and at first follow-up (AUC 0.71, 95% CI 0.64–0.78). Follow-up haemodynamics and multidimensional risk assessment had greater prognostic significance than at baseline in SSc-PAH. For newly diagnosed patients with systemic sclerosis-associated PAH, some haemodynamic variables, particularly the stroke volume index, and a multidimensional risk assessment were more useful during early follow-up than at baseline http://ow.ly/LUuj30lrvfW